The science of murder - Kaufman, Brian (Boston, Mass. : WBGH Educational Foundation, 1981)
Examines the reality of murder, including the social distress and its causes and the clinical expertise needed to determine proof and responsibility. Studies the work of a medical examiner, the police, a pathologist, and laboratory technicians and discussions by forensic psychiatrists and convicted murders
Keywords: Murder; Criminal investigation; Criminal psychology